2021
DOI: 10.1016/j.jds.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin in calcified matrices of odontogenic cysts and odontogenic tumors: An immunohistochemical study

Abstract: Background/purpose There are few studies comparing the expression of enamel proteins, such as amelogenin, and cytokeratins in cyst and odontogenic tumors like in ameloblastoma and odontogenic keratocyst, indicating that amelogenin could be a potential biomarker for the aggressiveness in the odontogenic tumors. The aim of this study was to evaluate if the expression of amelogenin, cytokeratin AE1/AE3 (CKAE1/AE3) and cytokeratin 14 (CK14) in cysts and odontogenic tumors with calcified matrices such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Conversely, their results of reduced enamel epithelium and dental lamina were with ours of dental germs. On the contrary, Zakaraia et al [1] and Urzua et al [23] reported positive AMEL immunoexpression in ABs.…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, their results of reduced enamel epithelium and dental lamina were with ours of dental germs. On the contrary, Zakaraia et al [1] and Urzua et al [23] reported positive AMEL immunoexpression in ABs.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, developing novel scaffold materials that meet the needs of a wide range of patients is critically needed. Current findings suggest that enamel can induce the regeneration of periodontal support tissues (gingival, periodontal, osseous, and alveolar bone) [7][8][9] ; however, AM cannot persist for long periods in areas of periodontal tissue defects [11,12] . To solve this issue, in this study we compounded AM with a drug-loaded CA hydrogel and the outcome was successful.…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages also produce a large number of growth factors and chemokines related to bone healing, contributing to the homing and migration of bone marrow mesenchymal stem cells (BMSCs) and bone healing. Amelogenin (AM) is an essential component of enamel matrix proteins, and current findings suggest that it can induce periodontal support tissue regeneration [7][8][9] ; however, studies on its mechanism of action are rare. Yamamichi et al .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Addressing this, our study aimed to develop a novel scaffold material that can cater to a broad patient spectrum. Current findings suggest that enamel can induce the regeneration of periodontal support tissues (gingival, periodontal, osseous, and alveolar bone); 7–9 however, AM tends to degrade rapidly in periodontal tissue defect sites. 11,12 To mitigate this, we incorporated AM into a drug-loaded CA hydrogel, achieving promising results in addressing this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Amelogenin (AM) is an essential component of enamel matrix proteins, and current ndings suggest that it can induce periodontal support tissue regeneration; [7][8][9] however, studies on its mechanism of action are rare. Yamamichi et al showed that AM could induce M2 polarization and promote periodontal tissue healing and regeneration.…”
Section: Introductionmentioning
confidence: 99%